please solve this (v) problem
Attachments:
![](https://hi-static.z-dn.net/files/dcb/c91ce8a5d9a44be91dcf98a91b1ea0d6.jpg)
Answers
Answered by
2
x ^(-7/2) × 2x^(-1/2)
= {x^(-1/2) ÷ (x^3)} × 2x (-1/2)
let x^(-1/2) be a
then,
( a)/(a^3) × 2a
= (2a^2) / x^3
substitute for a
[2x^ {(-1/2)×(2)}] / {(x^3)}
= 2 x^(-1) /(x^3)
= 2 x^(-1 -3)
= 2x^(-4).
= {x^(-1/2) ÷ (x^3)} × 2x (-1/2)
let x^(-1/2) be a
then,
( a)/(a^3) × 2a
= (2a^2) / x^3
substitute for a
[2x^ {(-1/2)×(2)}] / {(x^3)}
= 2 x^(-1) /(x^3)
= 2 x^(-1 -3)
= 2x^(-4).
Answered by
2
Hope it helps you and you understand
Attachments:
![](https://hi-static.z-dn.net/files/d92/c7a9a3981e755221b3dc7e66ab2dfb1c.jpg)
allysia:
nice EXPLANATION
Similar questions